Encyclopedia of Chinese history - Dillon, Michael (Routledge Taylor & Francis Group, 2017)
"China has become accessible to the west in the last twenty years in a way that was not possible in the previous thirty. The number of westerners travelling to China to study, for business or for tourism has increased dramatically and there has been a corresponding increase in interest in Chinese culture, society and economy and increasing coverage of contemporary China in the media. Our understanding of China's history has also been evolving. The study of history in the People's Republic of China during the Mao Zedong period was strictly regulated and primary sources were rarely available to westerners or even to most Chinese historians. Now that the Chinese archives are open to researchers, there is a growing body of academic expertise on history in China that is open to western analysis and historical methods. This has in many ways changed the way that Chinese history, particularly the modern period, is viewed. The Encyclopedia of Chinese History covers the entire span of Chinese history from the period known primarily through archaeology to the present day. Treating Chinese history in the broadest sense, the Encyclopedia includes coverage of the frontier regions of Manchuria, Mongolia, Xinjiang and Tibet that have played such an important role in the history of China Proper and will also include material on Taiwan, and on the Chinese diaspora. In A-Z format with entries written by experts in the field of Chinese Studies, the Encyclopedia will be an invaluable resource for students of Chinese history, politics and culture."--Provided by publisher
Includes bibliographical references and index
Keywords: China -- History -- Encyclopedias; Wörterbuch; Enzyklopädie; Geschichte; China